Communication Pattern of Intelligence and Action Field of Class I Special Immigration Office TPI Makassar in Supervising Foreigners - Wahidin, Ikhsan; Samad, Abdul; Sukmarini, Andi Vita (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to examine, identify and describe the communication patterns of the Intelligence and Enforcement Field of the Makassar Class I TPI Immigration Office in the supervision of foreigners. This research approach uses qualitative research. Data were obtained through observation, in-depth interviews, literature study and documentation. The research was conducted at the Makassar Class I TPI Immigration Office and Makassar Immigration Detention Center with the object of research being foreigners who have been examined by immigration officers. Data collection techniques using interview methods and data analysis techniques using the Miles and Huberman model. The results showed that in the communication pattern of immigration officers and foreigners at the Makassar Class I TPI Immigration Office was carried out directly with the interview method. The interview process is carried out with questions and answers between Immigration Officers and Foreigners with immigration officers being more dominant in the communication process. In the examination process, foreigners are given the opportunity to clarify their presence and activities as well as violations if there are suspected violations. The communication pattern formed in the supervision of foreigners is a chain communication pattern between Immigration Officers, foreigners and translators/guarantors if needed.